2002
DOI: 10.1046/j.1365-4362.2002.01446.x
|View full text |Cite
|
Sign up to set email alerts
|

Perception of men with androgenetic alopecia by women and nonbalding men in Korea: how the nonbald regard the bald

Abstract: In this study of Koreans, the perception of balding men by others was similar to the perception of balding men by themselves. It is likely that androgenetic alopecia adversely influences social interactions of those who are subject to it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…perception by others compounds the psychological problems suffered by balding men. A Korean study of the perception of balding men by women and non-balding men found that their negative perception of men with androgenetic alopecia was similar to the psychosocial effects reported by the patients themselves [59]. Of note a perception of bald men looking less attractive was found in more than 90% of subjects surveyed.…”
Section: Clinical Syndromementioning
confidence: 90%
See 1 more Smart Citation
“…perception by others compounds the psychological problems suffered by balding men. A Korean study of the perception of balding men by women and non-balding men found that their negative perception of men with androgenetic alopecia was similar to the psychosocial effects reported by the patients themselves [59]. Of note a perception of bald men looking less attractive was found in more than 90% of subjects surveyed.…”
Section: Clinical Syndromementioning
confidence: 90%
“…Hair is an essential part of a person's self-image and the consequences of androgenetic alopecia are predominantly psychological. Several studies show that the negative selfperception of balding patients is consistent between Western [57,58] and Asian cultures [59]. The negative effect of androgenetic alopecia is often trivialized or ignored by unaffected people [60].…”
Section: Clinical Syndromementioning
confidence: 98%
“…In most cultures, physical appearance affects social interactions. Conditions that alter appearance may result in psycho logical disadvantage [14,17]. Men with AGA are perceived to appear older than their age and less attractive by other nonbalding men and especially by women [17].…”
Section: Psychological Morbiditymentioning
confidence: 99%
“…[ 1 2 3 4 5 6 ] MPHL has a significant psychosocial effect and has been perceived as older and less attractive. [ 7 ] To better treat and monitor this condition, an accurate and practical classification with high degree of reproducibility is necessary. Various Classifications for Male Pattern Hair Loss has been proposed with various complexity.…”
Section: Introductionmentioning
confidence: 99%